Risk Governance of Offshore Oil and Gas Operations - Lindøe, Preben Hempel; Baram, Michael S.; Renn, Ortwin (Cambridge University Press, 2013)
This book evaluates and compares risk regulation and safety management for offshore oil and gas operations in the United States, United Kingdom, Norway and Australia. It provides an interdisciplinary approach with legal, technological and sociological perspectives on efforts to assess and prevent major accidents and improve safety performance. Presented in three parts, it begins with a review of the factors involved in designing, implementing and enforcing a regulatory regime for industrial safety. It then evaluates the four regimes exploring the contextual factors that influence their design and implementation, their reliance on industrial expertise and standards and the use of performance indicators. Finally the book assesses the resilience of the Norwegian regime, its capacity to keep pace with new technologies and emerging risks, respond to near miss incidents, encourage safety culture, incorporate vested rights of labor, and perform inspection and self-audit functions. This book is relevant for those in government, business and academia, and anyone involved in offshore safety issues.